Determination of Nurses' Job Satisfaction in Private Hospitals in Karawang and its Implications on Performance - Panjaitan, Saur; Hidayat, Rahmat (Yayasan Sinergi Kawula Muda, 2026)
Hospitals are organizations operating in the public health sector. Nurses are the most important part of a hospital. Therefore, nurses' performance in hospitals must be good. For nurses to work well, there must be job satisfaction from the nurses. The purpose of this study was to determine the effect of talent management and democratic leadership style on job satisfaction and its implementation on nurse performance in private hospitals in Karawang Regency, West Java with a sample of 205 respondents from 20 private hospitals. The researcher took samples from all of these hospitals. This study used the SEM method, by applying the steps of the SEM method. The researcher used the Lisrel 8.8 tool. In analyzing the data, the researcher used an analysis test by looking at the SLF value, GOF test, construct reliability, and extract validity. The results of this study indicate that talent management and democratic leadership have an effect on job satisfaction with a large influence of 53 and 27 percent. Meanwhile, on performance, talent management and democratic leadership style have no effect. Job satisfaction in this study has a large influence on performance with an SLF value of 1.00 and job satisfaction is a mediating variable that can mediate the variables of talent management and democratic leadership style on performance, because the influence of talent management and democratic leadership is greater when mediated by job satisfaction.